The fiscal system of Venezuela : a report - Shoup, Carl S.; Due, John F.; Fitch, Lyle C.; MacDougall Donald; Oldman Oliver S.; Surrey Stanley S. (Baltimore, Johns Hopkins Press, 1959)
A reform of the structure of income tax, with certain changes in administrative procedure, a revision of the customs duties and customs administration; repeal of the 'cinco por mil' tax; an increase in the tax on gasoline; and a strengthening of the municipal real estate tax in urban areas: these are the major tax recommendations in the report.
Includes index
osc 10/12/2018
Loans
Keywords: Finance, Public; Fiscal policy